Impact of electrochemical cells configuration on a reliable assessment of active electrode materials for Vanadium Redox Flow Batteries. (10th November 2022) - García-Alcalde, Laura; González, Zoraida; Concheso, Alejandro; Blanco, Clara; Santamaría, Ricardo
Abstract: On the search of active electrode materials for Vanadium Redox Flow Batteries (VRFBs) most of previously reported studies were more focused on the modification processes of carbon-based felts than on the assessment of their behaviour towards the redox reactions involved in the proper operation of the device. As a result, a quantitative comparison between those published results is still challenging due to the lack of rigorous information about the electrochemical protocols followed and the different cell geometries/configurations used. In this context, the design of a reliable protocol of electrochemical characterization of the different active electrode materials under evaluation, which should be subsequently agreed by the researchers working on this field, would accelerate the development of these key components of VRFBs. To achieve this goal, this work investigates on the influence of several key experimental parameters, as the felt compression percentage and the electrodes configuration in the electrochemical setup, on the electrochemical results to be obtained when assessing the behaviour of carbon-based felts towards the vanadium redox reactions of interest. The results obtained show a clear influence of both parameters on the electrical contact resistance and on the electrochemical signals recorded by means of cyclic voltammetry and impedance spectroscopy measurements. Consequently, the requirement of providing reliable and consistent electrochemical characterization protocols is highlighted.